Optimalisasi Program Nol Jamban di Bantaran Sungai Arut Kecamatan Arut Selatan - Noor, Akhmad Fauzianp; Hidayah, Ulul (REKSABUMI, 2023)
The Arut River is a river that flows in South Arut District, West Kotawaringin Regency, Central Kalimantan. Communities along the Arut River use the river for transportation and fishing; the community also uses the Arut River as latrines. The habitual behaviour of the open defecation community on the banks of the Arut River is of concern to the local government. Based on the Regulation of the Minister of Health of the Republic of Indonesia Number 03 of 2014 concerning STBM on the first pillar, namely STOP BABS, the West Kotawaringin Regency Government is promoting the Zero Latrine Movement Program. This program aims to stop the spread of diseases from open defecation and provide essential services to the community. This study aimed to formulate a strategy for optimizing the Zero Latrine Movement Program with a Community Participatory Approach in the Arut Riverbanks, South Arut District. The method used in this research is descriptive qualitative research,supported  by primary data and secondary data. Primary data were collected through observation and interviews, and secondary data  were in the form of an inventory of PUPR Office data for Kotawaringin Barat Regency. The study results found that the factors hindering the Optimization of the Zero Latrine Movement Program were the Budget/Funds, Infrastructure and Human Resources factors. The strategy that the government can implement to optimize  the zero-latrine program is to continue to approach and socialize, involve the private sector and local companies, and participate in the community.